"Giant R wave" electrocardiogram pattern during exercise treadmill test: A case report - Puebla-Rojo Victor (Journal of Medical Case Reports, 2011)
Abstract Introduction The exercise treadmill test is widely used in the evaluation of patients with suspected or known coronary artery disease. The typical ischemic response used to be ST-segment depression. Case presentation We describe a case of a 51-year-old Caucasian man with an unusual ischemic response during the exercise treadmill test: a "giant R wave" electrocardiogram pattern as a manifestation of hyperacute ischemia that resolved with sublingual nitroglycerin. Coronary catheterization showed a severe stenosis in a proximal dominant circumflex coronary artery. We hypothesize that, in this case, the "giant R wave" pattern was related to severe hyperacute ischemia due to coronary spasm superimposed on the atherosclerotic lesion, which probably caused complete occlusion of the artery. The patient was successfully treated with coronary percutaneous revascularization. Conclusions This is a dramatic and rare ischemic response during the exercise treadmill test, in which, a rapid administration of nitroglycerin can prevent life-threatening events.